Generation of microdissected DNA probes from metaphase chromosomes when chromosome identification by routine staining is impossible - K. S. Zadesenets; N. B. Rubtsov (Вавиловский журнал генетики и селекции)
Application of microdissected DNA libraries and DNA probes in numerous and various modern molecular cytogenetic studies showed them as an efficient and reliable tool in the analysis of chromosome reorganization during karyotypic evolution and in the diagnosis of human chromosome pathology. An important advantage of DNA probe generation by metaphase chromosome microdissection followed by sequence-independent polymerase chain reaction in comparison with the method of DNA probe generation using chromosome sorting is the possibility of DNA probe preparation from chromosomes of an individual sample without cell line establishment for the production of a large number of metaphase chromosomes. One of the main requirements for successful application of this technique is a possibility for identification of the chromosome of interest during its dissection and collection of its material from metaphase plates spread on the coverslip. In the present study, we developed and applied a technique for generation of microdissected DNA probes in the case when chromosome identification during microdissection appeared to be impossible. The technique was used for generation of two sets of Whole Chromosome Paints (WCPs) from all chromosomes of two species of free-living flatworms in the genus Macrostomum, M. mirumnovem and M. cliftonensis. The single-copy chromosome technique including separate collection of all chromosomes from one metaphase plate allowed us to generate WCPs that painted specifically the original chromosome by Chromosome In Situ Suppression Hybridization (CISS-Hybridization). CISS-Hybridization allowed identifying the original chromosome(s) used for DNA probe generation. Pooled WCPs derived from homologous chromosomes increased the intensity and specificity of chromosome painting provided by CISS-Hybridization. In the result, the obtained DNA probes appeared to be good enough for application in our studies devoted to analysis of karyotypic evolution in the genus Macrostomum and for analysis of chromosome rearrangements among the worms of laboratory cultures of M. mirumnovem.